Developing methods to prioritize in vitro drug combinations against Mycobacterium tuberculosis: fusidic acid as potential combination partner with known antitubercular agents - Omollo, Charles (Department of Chemistry, 2017)
The tuberculosis (TB) epidemic remains a major threat to public health globally, and is exacerbated by the escalating number of multi-drug resistant cases. These factors have highlighted the urgent need for new effective therapies or different approaches to augment the efficacy of current anti-TB drugs. Synergistic drug combinations present a feasible strategy towards expanding TB treatment options. Despite reported successes with combination screening, as well as the current reliance on combination therapy for TB, this approach remains largely underexplored. Evidence suggests that utilizing synergistic combinations might enable existing clinically-approved drugs to be readily re-purposed for TB treatment, including against multi-(MDR) and extensively- (XDR) drug resistant strains for current therapies are often ineffective. This thesis focused on the development and application of improved methods to identify and advance novel drug combinations for TB therapy. There were two key aspects to this work: firstly, exploring mechanisms of synergy between fusidic acid (FSA), a natural product antibiotic, and current anti-TB agents and, secondly, characterizing antibiotic action by delineating bacteriostatic and bactericidal compounds.